Trade liberalisation, changing forest management and roundwood trade in Europe - Kari Kangas (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper analyses the development of roundwood trade in Europe in the context of changes in supply and trading patterns due to liberalisation in European transitional economies (CEEC), nature-oriented forest management as well as prospective EU enlargement. First, it is studied whether roundwood imports have extended their share in apparent consumption in the EU and whether liberalisation in CEEC has changed the geographical composition of imports. Next, the development of the export structure of EU accession candidates is examined. Finally, rough assessments of the sustainability of roundwood production in CEEC as well as future of the trade flows in Europe are provided.
Keywords: F14; F15; F18; L73; P33; Q23; 330; European Union; accession candidates; roundwood; exports; imports; gravity models; Holz; Außenhandel; Forstwirtschaft; Handelsliberalisierung; EU-Staaten; Osteuropa